2010
DOI: 10.1186/1475-2875-9-276
|View full text |Cite
|
Sign up to set email alerts
|

Specific antibody responses against membrane proteins of erythrocytes infected by Plasmodium falciparum of individuals briefly exposed to malaria

Abstract: BackgroundPlasmodium falciparum infections could lead to severe malaria, principally in non-immune individuals as children and travellers from countries exempted of malaria. Severe malaria is often associated with the sequestration of P. falciparum-infected erythrocytes in deep micro-vascular beds via interactions between host endothelial receptors and parasite ligands expressed on the surface of the infected erythrocyte. Although, serological responses from individuals living in endemic areas against proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 75 publications
1
27
1
Order By: Relevance
“…The presence of circulating autoantibodies against RBC membrane proteins has already been described in malaria patients Wahlgren et al 1983). Moreover, we recently reported that non-immune healthy adults briefly exposed to malaria endemic areas mounted an antibody response against host proteins from iRBC membrane protein extracts, such as spectrin, adducin or host chaperone proteins (Fontaine et al 2010). These individuals had no history of clinical malaria, and only a minority exhibited clinical signs of a P. falciparum infection during their journeys.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The presence of circulating autoantibodies against RBC membrane proteins has already been described in malaria patients Wahlgren et al 1983). Moreover, we recently reported that non-immune healthy adults briefly exposed to malaria endemic areas mounted an antibody response against host proteins from iRBC membrane protein extracts, such as spectrin, adducin or host chaperone proteins (Fontaine et al 2010). These individuals had no history of clinical malaria, and only a minority exhibited clinical signs of a P. falciparum infection during their journeys.…”
Section: Discussionmentioning
confidence: 98%
“…Both P. falciparum strains were maintained in continuous culture in candle jars (Trager and Jensen 2005;Druilhe and Gentilini 1982). Parasites were cultured as previously described (Fontaine et al 2010). Monthly, six microsatellites were used to control clonality from each P. falciparum strain; their genotypic diversity was confirmed as previously described (Bogreau et al 2006).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations